2018
DOI: 10.1051/shsconf/20184001004
|View full text |Cite
|
Sign up to set email alerts
|

An overview on pedestrians involved in traffic accidents in Latvia: Years 2010-2014

Abstract: Latvian national road accident statistics shows that for the vulnerable road users’ situation is critical, since pedestrians are involved in more than a quarter of road traffic accidents. This paper gives an analysis on pedestrians involved in road traffic accidents based on the road safety accident database in Latvia for the years 2010–2014. The total number of cases does not change significantly, however there has been an increase in pedestrian fatality rates over the period. From the total number of traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The cause-effect relationship between violation of speed limits and pedestrian fatalities is also understood by the experts. Despite that Ukraine has highest level of pedestrian fatality (42%), the level of enforcement of the national speed limit law is the lowest (3 out of 10) [1,11].…”
Section: Resultsmentioning
confidence: 99%
“…The cause-effect relationship between violation of speed limits and pedestrian fatalities is also understood by the experts. Despite that Ukraine has highest level of pedestrian fatality (42%), the level of enforcement of the national speed limit law is the lowest (3 out of 10) [1,11].…”
Section: Resultsmentioning
confidence: 99%
“…Every year, tens of thousands of vehicle collisions worldwide result in the death of a large number of two-wheeler cyclists, while causing huge economic losses [4]. In automobile-two-wheeler crashes, head injuries are the most common type of injury that causes fatalities and serious injuries among cyclists [5][6][7]. Studies have shown that wearing a helmet can effectively reduce head injuries suffered by cyclists in traffic accidents [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Every year, tens of thousands of vehicle collisions worldwide result in the death of a large number of two-wheeler cyclists, while causing huge economic losses [ 4 ]. In automobile-two-wheeler crashes, head injuries are the most common type of injury that cause fatalities and serious injuries among cyclists [ 5 , 6 , 7 ]. Studies have shown that wearing a helmet can effectively reduce head injuries suffered by cyclists in traffic accidents [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%